2021
DOI: 10.3390/biomedicines9070712
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of the Addition of Fibroblast Growth Factor-2 to Biodegradable Gelatin/Magnesium-Doped Calcium Silicate Hybrid 3D-Printed Scaffold with Enhanced Osteogenic Capabilities for Critical Bone Defect Restoration

Abstract: Worldwide, the number of bone fractures due to traumatic and accidental injuries is increasing exponentially. In fact, repairing critical large bone defects remains challenging due to a high risk of delayed union or even nonunion. Among the many bioceramics available for clinical use, calcium silicate-based (CS) bioceramics have gained popularity due to their good bioactivity and ability to stimulate cell behavior. In order to improve the shortcomings of 3D-printed ceramic scaffolds, which do not easily carry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Multiple types of biomaterials such as hydrogel, ceramic, and metal have since been explored for clinical bone regeneration and repair [ 12 , 13 , 14 ]. Calcium silicate-based ceramic (CS) has demonstrated its expressed biocompatibility and osteoinductivity compared with calcium phosphate bioceramic, which can urge osteogenic differentiation of pre-osteoblasts by promoting the secretion of functional proteins [ 15 , 16 ]. Among them, the main reason is the presence of the silicon ion (Si), which has been found to modulate the activity of cellular behaviors, such as proliferation, differentiation, and mineralization of primary cells [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple types of biomaterials such as hydrogel, ceramic, and metal have since been explored for clinical bone regeneration and repair [ 12 , 13 , 14 ]. Calcium silicate-based ceramic (CS) has demonstrated its expressed biocompatibility and osteoinductivity compared with calcium phosphate bioceramic, which can urge osteogenic differentiation of pre-osteoblasts by promoting the secretion of functional proteins [ 15 , 16 ]. Among them, the main reason is the presence of the silicon ion (Si), which has been found to modulate the activity of cellular behaviors, such as proliferation, differentiation, and mineralization of primary cells [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sufficient porosity is needed to accommodate cell proliferation and differentiation, which will eventually enhance tissue formation [ 26 ]. It is also desirable for a scaffold to have high interconnectivity between pores for uniform cell seeding and distribution, nutrition support and efficient waste removal [ 27 ]. A good scaffold for hard tissue engineering should have approximately 100–400 µm of well-interconnected pores to support good tissue regeneration and the addition of CA into MTA did not affect such desired characteristics of the scaffolds.…”
Section: Resultsmentioning
confidence: 99%
“…The identification and development of suitable bioscaffolds capable of supporting hDPSCs and enhancing odontogenesis are critical aspects of tooth engineering [11]. An ideal scaffold should be non-toxic, yet bioactive, and most importantly, it should be able to provide a 3D microenvironment similar to native tissues that supports cell growth, proliferation, and differentiation [12][13][14]. In recent years, several studies demonstrated that the microenvironment of a 3D hydrogel is closer to the real situation than the 2D culture method because it can improve the proliferation and differentiation functions during the cell culture process [15].…”
Section: Introductionmentioning
confidence: 99%